Psychological needs with life satisfaction and self-esteem in three age groups - Španić, Ana Marija (2011)
Many studies have shown that psychological needs are basic constructs in explaining important life outcomes. The present study compares satisfaction of psychological needs in different age groups and investigates if psychological needs can predict life satisfaction and self-esteem. Data was collected on high school students (N=219, M=15.7, SD=0.45), university students (N=197, M=23.1, SD=0.81) and adults (N=182, M=40.2, SD=3.42). Participants completed Basic Psychological Needs Scale, Satisfaction with Life Scale and Self- esteem scale. Age differences were not found for need for competence, but for autonomy high school students had higher scores than other age groups, and for relatedness both high school and university students scored higher than adults. Psychological needs predicted both life satisfaction and self-esteem, explaining 26% and 40% of variance in high school students, 38% and 50% in university students, 49% and 35% in adults. Results are discussed according to the Self- Determination Theory.